2006
DOI: 10.1063/1.2374866
|View full text |Cite
|
Sign up to set email alerts
|

Thermoluminescence properties of ZnO and ZnO:Yb nanophosphors

Abstract: ZnO and ZnO:Yb thermoluminescence nanophosphors have been developed and tested under beta radiation. Spherical nanoparticles of sizes ranging from 130to1200nm were prepared through a glycol mediated chemical synthesis. The Yb doping had a thermoluminescence quenching effect compared to undoped ZnO. The 5% Yb concentration produced a low fading, a single thermoluminescence glow peak structure, and a dose linearity behavior adequate for thermoluminescence dosimetry applications. The ZnO:Yb nanophosphor has a gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…The difference with the recent studies of Pal et al [41] and Liu et al [42], was mainly the amount of the doping material. Nevertheless, transmittance spectra showed that thin films are transparent at the visible domain concordantly with these two studies [41,42]. Unexpectedly, all the doped thin films show caxis oriented (0 0 2) plane.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The difference with the recent studies of Pal et al [41] and Liu et al [42], was mainly the amount of the doping material. Nevertheless, transmittance spectra showed that thin films are transparent at the visible domain concordantly with these two studies [41,42]. Unexpectedly, all the doped thin films show caxis oriented (0 0 2) plane.…”
Section: Resultsmentioning
confidence: 80%
“…Oppositely to the recent studies on common ytterbium-doped materials, like Yb-doped alumino-silicate-based materials for laser fibres [31][32][33][34][35][36], BaY 2 F 8 and BaYb 2 F 8 -like fluoride crystals [37,38], Yb-doped oxide phosphors [39] and Yb-related organic application [40]. The difference with the recent studies of Pal et al [41] and Liu et al [42], was mainly the amount of the doping material. Nevertheless, transmittance spectra showed that thin films are transparent at the visible domain concordantly with these two studies [41,42].…”
Section: Resultsmentioning
confidence: 88%
“…After the recent success of Yb doping in ZnO nanoparticles reported by our group, 14 we prepared TiO 2 nanoparticles doped with Yb +3 ions. Though the ionic radius of Yb +3 ions (1.008 Å) is relatively larger than that of Ti +4 * Authors to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…The additional rare-earth elements also contribute to the high deposition rate without sacrificing the process stability. Besides, the rare-earth elements could not only be activated to improve the conductivity of AZO films [26], [27], but also be considered as the luminescent centers in the AZO host matrix [28], [29]. These unique features make the rare-earth doped AZO films investigated popularly.…”
mentioning
confidence: 98%